Carbon Dioxide Capture by MgO-modified MCM-41 Materials - Xin Fu; Ning Zhao; Junping Li; Fukui Xiao; Wei Wei; Yuhan Sun (Adsorption Science & Technology)
MgO/MCM-41 materials with weak basic sites were synthesized by dispersing MgO onto mesoporous Si-MCM-41. Such MgO-modified MCM-41 materials were characterized by Fourier-transform infrared spectroscopy (FT-IR), temperature programmed desorption (TPD), X-ray diffraction (XRD) and N 2 adsorption/desorption measurements. The results indicated that the surface area, pore size and pore volume of the materials decreased with the introduction of MgO. Their CO 2 uptakes could be significantly improved when the MgO loading was increased from 0 wt% to 20 wt%. CO 2 -TPD and in situ FT-IR measurements showed that the materials possessed weak basic sites which could react with CO 2 to form bicarbonate species and thereby improve the CO 2 uptake. As a result, the adsorbed CO 2 could be desorbed completely from the sample at 200 °C. In addition, the MgO/MCM-41 materials had a high thermal stability and showed promising performances in practical applications.